The Influence Of Social Influence And Live Streaming On Product Purchasing Decisions Through Tiktok Shop - Putri Putri; Wahyuningsih Wahyuningsih; Elimawaty Rombe; Wiri Wirastuti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The purpose of this study is to partially determine the positive and significant effect of social influence and live streaming on purchasing decisions and to determine the effect of social influence and live streaming simultaneously on purchasing decisions. The research method applied is a quantitative approach. The population in this study were TikTok Shop users who live in Palu City. This study involved 120 respondents as a sample obtained using a non-probability sampling method with purposive sampling technique. Data collection was carried out by distributing questionnaires via google form, then analyzed using SPSS 26 with the multiple linear analysis method. The research findings show that social influence has a positive and significant effect on purchasing decisions, live streaming also has a positive and significant effect on purchasing decisions, social influence and live straming together have a positive and significant effect on purchasing decisions.